Inorganic Waste Management in Decreasing Maya Index and Entomology Index of Mosquito Larvae - Zuhriyah, Lilik; Satoto, Tri Baskoro Tunggul; Kusnanto, Hari (Jurnal Kesehatan Masyarakat, 2016)
Inorganic waste management through Malang Waste Bank (BSM) is expected to reduce the risk of Dengue Hemorrhagic Fever (DHF). However, the number of neighborhood groups (RT) which become BSM participant varies. The problem is whether or not this variation will result in different entomology of mosquito larvae indexes. The purpose of this study is to prove the role of inorganic waste management to the risk of DHF transmission. Longitudinal survey was conducted weekly for 4 months in 2013 in six villages with the highest dengue cases in the city of Malang. Villages were classified into 3 types of membership of Malang Waste Bank (BSM). The result shows that the number of controllable containers is more than disposable container. Kruskal Wallis test mentions that the House Index (HI), Breteau Index (BI), Container Index (CI), and Density Index (DI) of the three villages are significantly different (p <0.05), while MI is not different. MI is related to all of mosquito larvae entomological indexes except with HI. Therefore, it can be concluded that the level of cleanliness of an area (MI) can be an indicator of the high index of mosquito larvae entomological indexes.